COMPARISON OF EFFICIENCY OF MIDDLE MOLECULAR MASS UREMIC TOXIN REMOVAL BETWEEN HIGH-FLUX HEMODIALYSIS AND POSTDILUTION ONLINE HEMODIAFILTRATION - Petrović, Dejan (Medicinski časopis, 2021)
INTRODUCTION. Conventional high-flux hemodialysis effectively removes uremic toxins of middle molecular weight of 0.5-15 (20) kDa, while postdilution online hemodiafiltration effectively removes uremic toxins of medium molecular weight in the range of 0.5-60 kDa. AIM. The aim of the study was to compare the efficacy of β2-microglobulin removal from patient serum during a single session of conventional high-flux hemodialysis and postdilution online hemodiafiltration. METHOD. Eighty-five patients treated with conventional high-flux hemodialysis and thirty patients treated with postdilution online hemodiafiltration were examined. The main parameter for assessing the removal efficiency of middle molecular weight uremic toxins was serum β2-microglobulin concentration before and after a single session of conventional high-flux hemodialysis and postdilution online hemodiafiltration. The following were used for statistical analysis: Kolmogorov-Smirnov test, Student's T test and Mann-Whitney U test. RESULTS. In patients treated with postdilution online hemodiafiltration, the average total convective volume was 21.38 ± 2.97 liters per session. The β2-microglobulin reduction index for the FX CorDiax 600 dialysis membrane was 61.76 ± 7.32%, for the FX CorDiax 800 dialysis membrane 74.69 ± 6.51%. The albumin reduction index for the FX CorDiax 600 membrane was 3.48 ± 1.28, for the FX CorDiax 800 dialysis membrane 6.01 ± 2.97%. Between the albumin reduction index, for two different dialysis modalities and two different dialysis membranes, there is a highly statistically significant difference (p < 0.01). CONCLUSION. Postdilution online hemodiafiltration is more efficient in removing β2-microglobulin from patient serum, compared to conventional high-flux hemodialysis. Albumin loss during a single session of high-flux hemodialysis is lower compared to a single session of postdilution online hemodiafiltration. With both dialysis modalities, albumin loss is less than 4.0 g/4h. High-flux hemodialysis effectively prevents the development of dialysis-related amyloidosis, while postdilution online hemodiafiltration effectively prevents not only the development of dialysis-related amyloidosis, but also the development of resistance to erythropoietin and atherosclerotic cardiovascular diseases in the population treated with regular dialysis.
Keywords: online hemodiafiltration, conventional high-flux hemodialysis, uremic toxins, albumin, β2-microglobulin, dialysis membrane